Composite material based on ZnO functional compound, preparation method and metal battery

By coating the surface of the metal battery anode with a ZnO functional compound coating, the problems of ion deposition and migration of metal anodes over a wide temperature range are solved, achieving rapid and uniform deposition and efficient migration of lithium ions, thus improving the rate performance of the battery.

CN119297244APending Publication Date: 2025-01-10CHANGSHA GUNENG NEW ENERGY TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411458225.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

Existing metal anodes in secondary batteries suffer from slow ion deposition/stripping kinetics, easy reaction with electrolytes, dendrite growth, and interface problems, which limit their application in a wide temperature range.

Method used

By employing a composite material based on ZnO functional compounds, the coating exhibits both pyroelectricity and magnetism, thereby improving the rate performance of metal batteries by regulating lithium-ion distribution and migration pathways.

Benefits of technology

This improves the deposition rate and uniformity of lithium ions over a wide temperature range, thereby enhancing the rate performance of metal batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119297244A_ABST
    Figure CN119297244A_ABST
Patent Text Reader

Abstract

The invention provides a composite material based on a ZnO functional compound, a preparation method and a metal battery. The composite material comprises a substrate material and a ZnO functional compound coating arranged on the surface of the substrate material, the ZnO functional compound coating contains a ZnO functional compound, the ZnO functional compound has pyroelectricity and magnetism, and the preparation method of the ZnO functional compound comprises the following steps: designing a ZnO-based compound, then compounding the ZnO-based compound onto the surface of a metal negative electrode by adopting an ALD (atomic layer deposition) method or a spraying method and the like, and drying to obtain the ZnO compound-based composite material. The preparation method is simple and controllable, the pyroelectric property of the ZnO-based compound ensures rapid ion migration at low temperature, and the magnetic property of the ZnO-based compound ensures high ion dissociation capability and uniform distribution at an interface, so that the metal battery containing the composite material provided by the invention has excellent wide-temperature-range electrochemical property.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of secondary metal batteries, and in particular relates to a composite material based on a ZnO functional compound, a preparation method and a metal battery. Background Art

[0002] With the continuous development of modern society, rechargeable secondary batteries have been gradually applied to various fields of our lives. However, the currently widely used secondary batteries are facing the key bottleneck problem of improving energy density. The most effective way to solve this problem is to use a metal anode with high capacity to replace the carbon-based or silicon-based anode.

[0003] However, there are still a lot of problems in the application of metal anodes at this stage, such as (1) the metal anode is a host-free anode based on the conversion mode, and its ion deposition / stripping kinetics are slow, resulting in poor rate performance; (2) highly active metals tend to react violently with electrolytes and induce uneven ion deposition and dendrite nucleation and growth, which can easily induce safety problems. At the same time, under complex working conditions (low temperature, high temperature, overcharge and overdischarge, etc.), the interface problems of metal batteries will be further deteriorated, greatly limiting their large-scale application. Therefore, it is necessary to comprehensively regulate the ion distribution at the interface and increase the ion migration rate to improve the wide temperature range rate performance of metal batteries. Summary of the invention

[0004] In order to solve the problems of solid-solid interface instability, dendrite growth and interface side reactions when metal batteries are used under wide temperature range conditions, the first purpose of the present invention is to provide a composite material based on ZnO functional compounds, which promotes the dissociation of electrolyte salts and regulates ion distribution and migration through the design of the functional interface layer of the composite material to improve the rate performance of metal batteries under wide temperature conditions.

[0005] The second object of the present invention is to provide a method for preparing a composite material based on a ZnO functional compound. The preparation method provided by the present invention is simple to operate and has great practical application value.

[0006] A third object of the present invention is to provide a metal battery, comprising the composite material.

[0007] In order to achieve the above object, the present invention provides the following technical solutions:

[0008] The present invention provides a composite material based on a ZnO functional compound, comprising a base material and a ZnO functional compound coating disposed on the surface of the base material;

[0009] The ZnO functional compound coating contains a ZnO functional compound, the chemical formula of which is Zn x M 1-xO, wherein x>0.7; the M is selected from at least one of Al, Mn, Mg, Ni, and Ba;

[0010] The ZnO functional compound is a single crystal solid solution structure.

[0011] The ZnO functional compound has pyroelectricity and magnetism.

[0012] The composite material based on the ZnO functional compound provided by the present invention is provided with a ZnO functional compound coating, wherein the ZnO functional compound has both pyroelectricity and magnetism, has a high dielectric constant within a wide temperature range, can promote the dissociation of lithium salts, and its magnetism can promote the uniform distribution of ions; its pyroelectricity promotes its polarization, regulates the lithium ion pathway, that is, regulates the migration path and migration speed, induces the rapid deposition of lithium ions, thereby improving the rate performance of the metal battery within a wide temperature range.

[0013] In the present invention, the chemical formula of the ZnO functional compound is Zn x M 1-x O, where x>0.7, has less doping with foreign elements, and the doping elements replace the position of Zn without entering the lattice gap. It has a single crystal solid solution structure and has both pyroelectricity and magnetism.

[0014] In a preferred embodiment, the substrate material is selected from one of lithium metal, sodium metal, zinc metal, magnesium metal and potassium metal.

[0015] In a preferred solution, the thickness of the ZnO functional compound coating is 1-500 nm. In the present invention, the thickness of the ZnO functional compound coating cannot be too thick, as too thick a thickness will lead to lithium ion migration path process and loss during the migration process.

[0016] The present invention discloses a method for preparing a composite metal negative electrode based on a ZnO functional compound, wherein a Zn source and a doping element source are deposited on a substrate material by atomic layer deposition (ALD);

[0017] The doping element source is selected from at least one of Al, Mn, Mg, Ni and Ba.

[0018] In a preferred embodiment, during the atomic layer deposition, the deposition temperature is controlled to be 100-200°C, the deposition rate is 0.01-0.5 nm / cycle, and the argon gas flow rate is 100-200 cm 3 / min, pulse time is 0.01~10s.

[0019] The present invention discloses a method for preparing a composite material based on a ZnO functional compound, comprising adding a binder into an organic solvent to obtain a solution A, adding the ZnO functional compound into the solution A to obtain a suspension B, and coating the suspension B on the surface of a substrate material to obtain a composite material;

[0020] The ZnO functional compound is selected from Zn x M 1-x O, wherein x>0.7; the M is selected from at least one of Al, Mn, Mg, Ni, and Ba;

[0021] The binder is at least one selected from polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene (P(VDF-HFP)), and poly(vinylidene fluoride-trifluoroethylene-chlorotrifluoroethylene) (P(VDF-TrFE-CTFE)).

[0022] The above preparation method directly uses a material with thermoelectric properties as a binder, mixes it with a ZnO functional compound, and then coats it on the surface of a base material to obtain a uniform thermoelectric material layer, thereby improving performance consistency.

[0023] In a preferred embodiment, the organic solvent is selected from at least one of N-methylpyrrolidone (NMP), N,N-dimethylformamide (DMF) and tetrahydrofuran.

[0024] In a preferred embodiment, in the solution A, the mass ratio of the binder to the organic solvent is 0.1:0.5 to 1. When the mass ratio of the binder to the organic solvent is controlled within this range, the coating performance is optimal. If there is too much binder, the slurry becomes viscous, which is difficult to coat and easily blocks the diaphragm pores; if there is too little binder, the adhesion is weak and the ZnO functional compound may fall off.

[0025] In a preferred embodiment, the binder is added into an organic solvent and stirred at 45-60° C. to obtain solution A.

[0026] In the present invention, the added ZnO functional compound is prepared by element doping.

[0027] In a preferred embodiment, the ZnO functional compound has a hexagonal single crystal structure and a grain size of 1 to 200 nm.

[0028] The hexagonal single crystal structure ZnO functional compound added in the present invention has the properties of both the pyroelectricity of thermoelectric materials and the magnetism and high dielectric constant of magnetic materials.

[0029] In a preferred embodiment, in the suspension B, the mass ratio of the binder to the ZnO functional compound is 0.05-0.2:0.8-0.95, preferably 0.05-0.1:0.1-0.9.

[0030] By controlling the mass ratio of the binder to the ZnO functional compound within the above range, it can have a good adhesion effect without causing the binder to cover the ZnO functional compound crystals, thereby having the best performance. If too much binder is added, it is easy to cover the crystals, and the inorganic material is not easy to perform its properties. Too little binder will not allow adhesion.

[0031] In a preferred embodiment, the coating method is selected from spin coating, scraper coating, dip coating and spray coating.

[0032] In a preferred embodiment, after the suspension B is coated on the metal substrate, it is dried at 60-80° C. for 6-20 hours to obtain the composite material.

[0033] The present invention also provides a metal battery, wherein the metal battery adopts the composite material as a negative electrode.

[0034] Preferably, the ZnO functional compound coating in the composite material faces the positive electrode side of the metal battery.

[0035] Preferably, the metal battery is an alkali metal secondary battery.

[0036] The metal battery provided by the present invention has a ZnO functional compound with a high dielectric constant that can promote the dissociation of lithium salts within a wide temperature range, and its magnetism can promote the uniform distribution of ions; its pyroelectricity promotes its polarization and induces the rapid deposition of lithium ions, thereby improving the wide temperature range performance of the metal battery.

[0037] Beneficial Effects

[0038] The composite material based on the ZnO functional compound provided by the present invention is provided with a ZnO functional compound coating, wherein the ZnO functional compound has both pyroelectricity and magnetism, has a high dielectric constant within a wide temperature range, can promote the dissociation of lithium salts, and its magnetism can promote the uniform distribution of ions; its pyroelectricity promotes its polarization, regulates the lithium ion pathway, that is, regulates the migration path and migration speed, induces the rapid deposition of lithium ions, thereby improving the rate performance of the metal battery within a wide temperature range. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 Performance comparison chart of Example 1 and Comparative Example 1 at low temperature -40°C. DETAILED DESCRIPTION

[0040] Example 1

[0041] Synthesis of element-doped Zn by high temperature sintering 0.9 Al 0.1 O. Among them Zn 0.9 Al 0.1 The particle size of O is 30 nm, and it has a hexagonal single crystal solid solution structure.

[0042] Prepare coating slurry: control the mass ratio of binder PVDF and DMF to 0.05:1, mix at 50℃ to form a solution; then add Zn 0.9 Al 0.1 O, control PVDF and Zn 0.9 Al 0.1 O mass ratio is 0.05:0.95, and PVDF+Zn 0.9 Al 0.1 O=1, after stirring to obtain a mixed slurry, the mixed slurry was sprayed on the surface of the metal lithium negative electrode in a drying workshop by a spraying method, and then vacuum dried at 60°C for 10 hours to obtain Zn 0.9 Al 0.1 O composite lithium metal anode with a coating thickness of 200 nm.

[0043] High nickel ternary NCM811 was used as the positive electrode, and the mass ratio of NCM811: carbon black: PVDF was 8:1:1. They were mixed evenly to form a slurry, which was evenly coated on aluminum foil and cut into positive electrode sheets with a diameter of 12 mm. .9 Fe 0.1 O composite lithium metal was used as the negative electrode and polypropylene film was used as the separator, and a CR2016 button battery was assembled in a glove box, which is the battery of Example 1.

[0044] For comparison, the battery of Comparative Example 1 uses metal lithium strips of the same specifications and is assembled into a CR2016 button battery under the same conditions. The above battery is subjected to charge and discharge cycle tests under the same test equipment and test conditions, wherein the voltage range of the full battery test is 3 to 4.3V and the test temperature is -40°C. Figure 1 The battery capacity of Example 1 is 103.8 mAh g at a current density of 1 C. -1 After 200 cycles, the capacity is still 100.2 mAh g -1 , while the capacity of comparative example 1 at 1C is only 42.4 mAh g -1 After 200 cycles, the capacity is 40.5 mAh g -1 .

[0045] Embodiment 2:

[0046] Compared with Example 1, the only difference is that the coating uses Zn 0.9 Mn 0.1 O, its mass ratio remains unchanged. Its capacity is 100.2 mAh g at a current density of 1C. -1 After 200 cycles, the capacity is still 98.3 mAh g -1 .

[0047] Embodiment 3:

[0048] Compared with Example 1, the only difference is that PVDF and Zn 0.9 Mn 0.1 The ratio of O was changed to 0.15:0.85, and the mass ratio remained unchanged. Its capacity reached 96.5 mAh g at a current density of 1C. -1 After 200 cycles, the capacity is still 94.1 mAh g -1 .

[0049] Embodiment 4:

[0050] Compared with Example 1, the only difference is that the composite metal negative electrode is prepared by ALD method, the deposition temperature is 150°C, the purge time is 10s, the deposition rate is about 0.1nm / cycle, and the argon gas flow rate is 159cm 3 / min, pulse time 3s, its capacity at a current density of 1C is 101.3mAh g -1 After 200 cycles, the capacity is still 98.6 mAh g -1 .

[0051] Embodiment 5:

[0052] Compared with Example 1, the only difference is that the base material is a sodium metal negative electrode and the positive electrode material is a layered NaCu 1 / 3 Fe 1 / 3 Mn 1 / 3 O 2 The material has a capacity of 67.3 mAh g at a current density of 1C. -1 After 200 cycles, the capacity is still 64.1 mAhg -1 .

[0053] Comparative Example 1

[0054] The battery uses a metal lithium strip with the same specifications as in Example 1, except that it is not coated and modified as the negative electrode.

[0055] Comparative Example 2:

[0056] Compared with Example 5, the only difference is that the substrate material is an uncoated sodium metal negative electrode and the positive electrode material is a layered NaCu 1 / 3 Fe 1 / 3 Mn 1 / 3 O 2 The material has a capacity of 36.1 mAh g at a current density of 1C. -1 After 200 cycles, the capacity is still 32.8 mAh g -1 .

[0057] Comparative Example 3:

[0058] Compared with Comparative Example 1, the only difference is that the coating is Zn 0.1 Al 0.9 O. Its capacity at a current density of 1C is 72.7 mAh g -1 After 200 cycles, the capacity is 70.3 mAh g -1 .

Claims

1. A composite material based on a ZnO functional compound, characterized in that: It comprises a substrate material and a ZnO functional compound coating disposed on the surface of the substrate material; The ZnO functional compound coating contains a ZnO functional compound, the chemical formula of which is Zn x M 1-x O, wherein x>0.7; the M is selected from at least one of Al, Mn, Mg, Ni, and Ba; The ZnO functional compound is a single crystal solid solution structure. The ZnO functional compound has pyroelectricity and magnetism.

2. A composite material based on a ZnO functional compound according to claim 1, characterized in that: The substrate material is selected from one of lithium metal, sodium metal, zinc metal, magnesium metal and potassium metal.

3. A composite material based on a ZnO functional compound according to claim 1 or 2, characterized in that: The thickness of the ZnO functional compound coating is 1 to 500 nm.

4. A method for preparing a composite material based on a ZnO functional compound according to any one of claims 1 to 3, characterized in that: Depositing a Zn source and a doping element source onto a substrate material by atomic layer deposition; The doping element source is selected from at least one of Al, Mn, Mg, Ni and Ba.

5. The method for preparing a composite material based on a ZnO functional compound according to claim 4, characterized in that: During the atomic layer deposition, the deposition temperature is controlled to be 100-200°C, the deposition rate is 0.01-0.5 nm / cycle, and the argon gas flow rate is 100-200 cm 3 / min, pulse time is 0.01~10s.

6. A method for preparing a composite material based on a ZnO functional compound according to any one of claims 1 to 3, characterized in that: Adding a binder into an organic solvent to obtain a solution A, adding a ZnO functional compound into the solution A to obtain a suspension B, and coating the suspension B on the surface of a substrate material to obtain a composite material; The ZnO functional compound is selected from Zn x M 1-x O, wherein x>0.7; the M is selected from at least one of Al, Mn, Mg, Ni, and Ba; The binder is selected from at least one of PVDF, P (VDF-HFP), and P (VDF-TrFE-CTFE).

7. The method for preparing a composite material based on a ZnO functional compound according to claim 6, characterized in that: The organic solvent is selected from at least one of NMP, DMF and tetrahydrofuran; In the solution A, the mass ratio of the binder to the organic solvent is 0.1:0.5-1; The binder is added into the organic solvent and stirred at 45-60° C. to obtain solution A.

8. The method for preparing a composite material based on a ZnO functional compound according to claim 6, characterized in that: The ZnO functional compound has a hexagonal single crystal structure and a grain size of 1 to 200 nm; In the suspension B, the mass ratio of the binder to the ZnO functional compound is 0.05-0.2:0.8-0.95; The coating method is selected from spin coating, scraper coating, dip coating, and spray coating; After the suspension B is coated on the metal substrate, it is dried at 60-80° C. for 6-20 hours to obtain a composite material.

9. A metal battery, characterized in that: The battery uses the composite material according to any one of claims 1 to 3 as the negative electrode.

10. A metal battery according to claim 9, characterized in that: The ZnO functional compound coating in the composite faces the positive electrode side of the metal battery.